2019
DOI: 10.1159/000497420
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing Enterocolitis, Gut Microbiota, and Brain Development: Role of the Brain-Gut Axis

Abstract: Necrotizing enterocolitis (NEC) is a relatively common disease in very-low-birth-weight infants and is associated with high mortality and morbidity. In survivors, neurodevelopmental impairment is frequently seen. The exact etiology remains largely to be elucidated, but microbiota are considered to play a major role in the development of NEC. Furthermore, emerging evidence exists that the microbiota is also of importance in brain function and development. Therefore, microbiota characterization has not only pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 64 publications
1
59
0
Order By: Relevance
“…In the context of human reproduction, it is conceivable that microbial metabolites, directly (e.g., via SCFA) or indirectly (e.g., acidification, alkalization, inflammatory responses), can either support (healthy microbiota) or upset (unbalanced/harmful microbiota) local cell-cell communication and tissue physiology and adaptation. As such, all relevant reproductive processes, including fertilization, implantation, placentation, immune tolerance, embryonal development, infant and adult health and may be harmfully altered by dysbiosis (167). Such geneenvironment interactions are yet to be examined in detail in the context of reproductive health and disease.…”
Section: Fundamental Research Developments and Directionsmentioning
confidence: 99%
“…In the context of human reproduction, it is conceivable that microbial metabolites, directly (e.g., via SCFA) or indirectly (e.g., acidification, alkalization, inflammatory responses), can either support (healthy microbiota) or upset (unbalanced/harmful microbiota) local cell-cell communication and tissue physiology and adaptation. As such, all relevant reproductive processes, including fertilization, implantation, placentation, immune tolerance, embryonal development, infant and adult health and may be harmfully altered by dysbiosis (167). Such geneenvironment interactions are yet to be examined in detail in the context of reproductive health and disease.…”
Section: Fundamental Research Developments and Directionsmentioning
confidence: 99%
“…NEC is the most common devastating gastrointestinal disease affecting the neonate, with a mortality rate between 15 and 30 % ( 40 ). It may affect both full-term and preterm neonates with the latter group having an increased risk.…”
Section: Mscs For the Treatment Of Neonatal Gut Diseasesmentioning
confidence: 99%
“…Additionally, the early composition of microbiota in preterm infants has been shown to be an indicator of the future occurrence of necrotizing enterocolitis (56). Animal studies have also demonstrated that the early microbiota composition is a key driver of the correct subsequent development of homeostasis, and of the host as a whole (5).…”
Section: Dysbiosis Of Gut Microbiotamentioning
confidence: 99%